EQUITY PREMIUM, INFLATION AND MARKET - Jarvis, Matthew John Kuys (My University, 2011)
This report investigated the linkages between three important components of the financial market in South Africa, namely equity risk premium, inflation and market volatility. While research has revealed strong relationships between these factors in other countries, little has been investigated in the local environment. Within the data, two key structural breaks in the equity premium were identified. When the data within these breaks was analysed, relationships between the three variables were found. Within the three periods defined, a mean equity premium of 7.87%, 10.43% and 0.1% respectively, was measured. Using well-known relationship-measuring statistical and regression analysis tools, the data were tested for possible relationships. Results showed that the relationships were not linear and as a result correlation and regression were of little use. However, qualitative and graphical analysis revealed that the equity premium moved in line with inflation, and market volatility was delayed by approximately one year
MBA - WBS
Keywords: Equity risk premium; Inflation; Market volatility